Recent Analysis of Carbon, Nitrogen, and Lignin Phenol Compositions in the Suspended Particulate Matters at Spermonde Archipelago, South Sulawesi, Indonesia: DOI: 10.32526/ennrj.18.2.2020.12 - Rustiah, Waode; Noor, Alfian; Maming, Maming; Lukman, Muhammad; Nurfadilah, Nurfadilah (Environment and Natural Resources Journal, 2019)
This study analyzed the composition of monomer lignin phenols and its derivatives at the Spermonde Archipelago, South Sulawesi-Indonesia. Water samples were collected in the dry season (June 2017) and the rainy season (January 2018) from the river estuaries of Tallo-Makassar, and Pangkep. Analysis of carbon and nitrogen contents was conducted by EA-IRMS (elemental analyzer-isotope ratio mass spectrometry), while lignin phenol was analyzed by Chromatography Gas-Mass Spectroscopy (GC-MS). Spatially, the six lignin phenols () content in the Tallo river estuary into several outermost islands is higher than of the Pangkep river mouth.  values in the rainy season were higher (0.92-2.30) than in the dry season (0.62-2.07). In the dry season, the range of values for ratios of syringyl/vanillyl and cinnamyl/vanillyl was 0.35 to 1.12 and 0.39 to 0.57 indicating a low contribution of angiosperm plant tissue. In the rainy season, the values of ratios for syringyl/vanillyl and cinnamyl/vanillyl ranged from 0.37 to 1.18 and 0.32 to 0.62. The syringyl/vanillyl ratio indicates the contribution of plant tissue to angiosperms. The cinnamyl/vanillyl value is greater than 0.1, indicating a significant contribution of non-woody plant tissue. Spatially, the range of syringyl/vanillyl and cinnamyl/vanillyl ratios at the estuary of the Tallo river (0.37 to 1.12 and 0.32 to 0.57) were higher than at the Pangkep river estuary (0.35 to 1.18 and 0.39 to 0.62).